2022
DOI: 10.3390/genes13122361
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Corticobasal Syndrome and Progressive Non-Fluent Aphasia (CBS-PNFA), with Variants in ATP7B, SETX, SORL1, and FOXP1 Genes

Abstract: Our aim was to analyze the phenotypic-genetic correlations in a patient diagnosed with early onset corticobasal syndrome with progressive non-fluent aphasia (CBS-PNFA), characterized by predominant apraxia of speech, accompanied by prominent right-sided upper-limb limb-kinetic apraxia, alien limb phenomenon, synkinesis, myoclonus, mild cortical sensory loss, and right-sided hemispatial neglect. Whole-exome sequencing (WES) identified rare single heterozygous variants in ATP7B (c.3207C>A), SORL1 (c.352G>A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…A similar case exhibiting the early onset of clinical PD symptoms in a heterozygous H1096Q mutation carrier was described in a cohort from Poland [ 137 ]. In Russia, another study reported a patient with early-onset PD and a novel mutation that led to the C1079G substitution of a conserved cysteine residue in the ATP7B nucleotide-binding domain [ 138 ].…”
Section: Proofs For the Existence Of The Link Between Copper Dyshomeo...mentioning
confidence: 71%
“…A similar case exhibiting the early onset of clinical PD symptoms in a heterozygous H1096Q mutation carrier was described in a cohort from Poland [ 137 ]. In Russia, another study reported a patient with early-onset PD and a novel mutation that led to the C1079G substitution of a conserved cysteine residue in the ATP7B nucleotide-binding domain [ 138 ].…”
Section: Proofs For the Existence Of The Link Between Copper Dyshomeo...mentioning
confidence: 71%
“…In their study, Katarzyna Gaweda-Walerych and colleagues analysed the phenotypic–genetic correlations in a patient diagnosed with early onset corticobasal syndrome with progressive non-fluent aphasia (CBS-PNFA) using a whole-exome sequencing (WES) approach [ 1 ]. They identified rare single heterozygous variants in the ATP7B , SORL1 , SETX , and FOXP1 genes, extending the complex clinical spectrum associated with variants in known disease genes and also supporting the hypothesis of oligogenic inheritance.…”
mentioning
confidence: 99%